Influência da analgesia de parto no desfecho obstétrico: estudo em uma maternidade pública brasileira - Bruno Carvalho Cunha de Leao (2016)
Rationale and objectives: labor pain is characterized by being acute-nociceptive and reported as severe by more than half of pregnant women. The regional analgesia of delivery is among the options, the most effective, but can also be associated with undesirable effects. Since the 1980s, researchers devoted to studying the relation between regional analgesia in labor and the obstetric outcome, especially by analyzing their influence on operative delivery rate, in instrumental vaginal or abdominal surgery. The latest data revisions focus on the technical variables of the intervention. The objective of this study was to evaluate the influence of lower local anesthetic doses in obstetric outcome. Method: prospective cohort study type of 181 pregnant women, ASA 2, regardless the parity and gestational age. The groups, regional analgesia and control were monitored throughout the delivery with follow-up to the seventh day of birth. The regional technique, epidural analgesia or combined, was previously established. The technical choice was made randomly in accordance with the presence of intervenor anesthesiologist. In the control group, only non-pharmacological methods of pain relief were used. The combined analgesic subgroup was analyzed in order to set its attributes, especially response curve and the incidence of fetal bradycardia for the dose used. Results: groups (91 regional analgesia and 90 control) were homogeneous in anthropometric, prenatal and admission analysis. The incidence of operative delivery was similar in the group that received regional analgesia (operative delivery: 20%; forceps: 7.8%; cesarean section: 12.2%) when compared to control (operative delivery: 29.7%; forceps: 16 , 5%; cesarean section: 14.3%) (p = 0.132; p = 0.073 and p = 0.682, respectively). In the multivariate analysis of the surgical outcome, the identified risk factors were: prolonged active phase (OR 4,55), nonreassuring fetal status (OR 10,87) and rotation dystocia (OR 15,87). Intrathecal bupivacaine 1.5 mcg associated with fentanyl 10 mcg promoted the reduction of about 70% in the pain scores of womenthat are in advanced labor and did not interfere in their deambulation ability. The incidence of fetal bradycardia was 6.7% after 30 minutes, being transient in all cases. Conclusion: regional analgesia at low doses in labor is able to promote satisfactory pain relief without significantly influence in the operative delivery rate. Delivery and its consequent prolonged pain are risk factors for the need of regional anesthesia and negative obstetrical outcome. Considering the studied population,it was concluded that it is unnecessary to initiate with the analgesia combined with doses higher than 1.5 mg in the presence of soluble opioid.